Optimizing Antibiotic Analysis: A Comprehensive Guide to HPLC Process of Assessment and Quantification - Manjeet Baliyan (International Journal of Antibiotics, 2024)
The history and uses of chromatography are thoroughly covered in this work, with an emphasis on the use of High-Pressure Liquid Chromatography (HPLC) in pharmaceutical analysis. Since its discovery by Russian botanist Mikhail Tswett in the 19th century, chromatography has undergone tremendous developments that have given rise to a variety of chromatography types and applications. The story follows the evolution historically, emphasizing Tswett's groundbreaking breakthrough in plant color classification and the birth of real chromatography. Chromatography types began to evolve in the 1940s, but Csaba Harwath's invention of the first liquid chromatographic apparatus in the 1960s was a turning point. The introduction of a flow cell for a UV detector by Kirkland in the late 1960s was a pivotal factor in the development of High-Performance Liquid Chromatography (HPLC). The paper covers the fundamentals of chromatography, the benefits of high-performance liquid chromatography (HPLC), and the different kinds of separation it provides, such as reverse and normal phase chromatography. The importance of buffers in HPLC separations is underlined, and the apparatus of HPLC is examined. The significance of solubility, absorbance, and water in mobile phases is addressed in detail, along with the selection of solvents, columns, and mobile phases in HPLC. In addition, the research explores degassing methods and emphasizes the need of system appropriateness criteria for method validation. The final section of the paper delves deeply into the creation of HPLC analytical methods, addressing important factors such mobile phase optimization, detector selection, and chromatography mode.
Keywords: Analytical Method Development; Chromatography; Gas Chromatography (GC); High-Pressure Liquid Chromatography (HPLC); Pharmaceutical Analysis